GARP dysfunction results in COPI displacement, depletion of Golgi v-SNAREs and calcium homeostasis proteins - Khakurel, Amrita; Kudlyk, Tetyana; Pokrovskaya, Irina; D’Souza, Zinia; Lupashin, Vladimir V. (Frontiers in Cell and Developmental Biology, 2022)
Golgi Associated Retrograde Protein (GARP) is an evolutionary conserved heterotetrameric protein complex that tethers endosome-derived vesicles and is vital for Golgi glycosylation. Microscopy and proteomic approaches were employed to investigate defects in Golgi physiology in RPE1 cells depleted for the GARP complex. Both cis and trans-Golgi compartments were significantly enlarged in GARP knock-out (KO) cells. Proteomic analysis of Golgi-enriched membranes revealed significant depletion of a subset of Golgi residents, including Ca2+ binding proteins, enzymes, and SNAREs. Validation of proteomics studies revealed that SDF4 and ATP2C1, related to Golgi calcium homeostasis, as well as intra-Golgi v-SNAREs GOSR1 and BET1L, were significantly depleted in GARP KO cells. Finding that GARP KO is more deleterious to Golgi physiology than deletion of GARP-sensitive v-SNAREs, prompted a detailed investigation of COPI trafficking machinery. We discovered that in GARP KO cells COPI is significantly displaced from the Golgi and partially relocalized to the ER-Golgi intermediate compartment (ERGIC). Moreover, COPI accessory proteins GOLPH3, ARFGAP1, GBF1, and BIG1 are also relocated to off-Golgi compartments. We propose that the dysregulation of COPI machinery, along with the depletion of Golgi v-SNAREs and alteration of Golgi Ca2+ homeostasis, are the major driving factors for the depletion of Golgi resident proteins, structural alterations, and glycosylation defects in GARP deficient cells.